Idārah Barāmij Ta’līm al-Lughah al-Arabiyyah fi Marhalah al-I’dād al-Lughawī bi Jāmi’ah al-Raayah Sukabumi (Arabic Language Education Program Management At The Language Preparation Level At STIBA Ar-Raayah Sukabumi) - Muhammad Umar; Taqyuddin Ibnu Syafi'i; Nuril Mufidah; Abdul Malik Karim Amrullah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
كل مؤسسات تعليمية تملك الإدارة الخاصة لتحقيق أهدافها، كذلك في تعليم اللغة العربية. لكن الواقع أن أكثير طلاب الجامعة لا يزالون يشكون من المشاكل المتعلقة بتعلم اللغة العربية، ومن أسباب ظهور تلك المشاكل في تعليم اللغة العربية بإندونيسيا هي قلة فعالية الإدارة التعليمية الجيدة. يهدف البحث إلى (1) وصف تخطيط برامج تعليم اللغة العربية لطلاب مرحلة الإعداد اللغوي بجامعة الراية سوكابومي، (2) ووصف تنظيمها، (3) ووصف تنفيذها، (4) ووصف تقويمها. استخدم البحث المدخل الكيفي على طريقة دراسة الحالة، ومصادر البيانات تتكون من رئيس القسم كالمصدر الأساسي والمعلم والطلاب كالمصدر الإضافي. وأسلوب جمع البيانات: 1) الملاحظة، 2) والمقابلة، 3) والوثائق. نتائج البحث: إدارة برامج تعليم اللغة العربية للطلاب في مرحلة الإعداد اللغوي بجامعة الراية سوكابومي تتفوق في: 1) أن التخطيط الذي أجري في جامعة الراية على أساس المشاورة، ويمر بالمراحل الآتية وهي الملاحظة والاجتماع وتنظيم العمل وتنفيذ البرامج. فتظهر الحاصلة أن مدة دراسية تستغرق ستة واحدة 2) أن تنظيم برامج تعليم اللغة العربية للطلاب في مرحلة الإعداد اللغوي بجامعة الراية سوكابومي له إدارة متميزة حيث يوجد فيها التنظيم الجيد الذي يسعى إلى تحقيق الأهداف التي قادها المدير باهتمام الإدارة العليا مع وكالة الشؤون والمعلمين. 3) أن تنفيذ البرامج بجامعة الراية يتميز بكثرة المواد اللغوية وتوفر المدة الدراسية. 4) أن الجامعة تقوم بتقويم تلك البرامج لتعرف مدى استيعاب الطلاب تجاه المواد التعليمية. AbstractEach educational institution has its own management to achieve its goals, as well as in teaching Arabic. However, in reality there are still many students who complain about problems related to learning Arabic, and one of the causes of these problems in Indonesia is the ineffectiveness of education management. This study aims to (1) describe the planning of an Arabic language education program for language preparation students at STIBA Ar-Raayah Sukabumi, (2) describe its management, (3) describe its implementation, (4) describe its evaluation. This study used a qualitative approach using the case study method, and the data sources consisted of the head of study program as the main source, teachers and students as additional sources. Methods for obtaining data: 1) observation, 2) interviews, 3) documentation. The research result: the management of the Arabic language education program for language preparation stage students at STIBA Ar-Raayah Sukabumi excels in: 1) Planning carried out at STIBA Ar-Raayah is based on deliberation, and through the next stages namely observation, meetings, work organization and program implementation, and the study period takes one year. 2) The implementation of this program has good administration where there are organizations trying to achieve goals led by the school principal and foundation officials as well as committee members and teachers. 3) The implementation of this program is marked by a large number of language materials and study periods. 4) The evaluation of these programs aims to determine students' understanding of educational material.